(untitled) (Research, Society and Development, 2021)
The need to develop teaching methodologies that are, in fact, efficient for the construction of knowledge is indisputable. In this perspective, there are indications in the literature that the cooperative learning methodology is configured as a viable alternative, which contributes to greater interaction between those involved and the development of social and cognitive skills. Thus, this work aims to analyze the perception of high school students in relation to the contributions of that methodology, outlining its positive and negative points. Data collection took place through the application of previously structured questionnaires following the ethical criteria of the research, in 1st and 3rd year classes, comprising a sample of 42 students, whose participation was voluntarily. The results obtained show that the vast majority of students are in favor of the teaching methodology in question, classifying it as a determinant for their learning process, as it improves school performance and promotes the socialization of knowledge. Therefore, it is concluded that despite the problems mentioned by some students, the use of the cooperative methodology promotes greater interaction among students, with significant results in increasing school performance and in the acquisition of social skills.